What are the macro-social health research priorities? - Narges Tabrizchi (Shahid Beheshti University of Medical Sciences, 2016)
Background: Setting research priorities is a scientific process to allocate resources to the best use. In low- and middle-income countries, allocation of limited resources to fundamental issues is more important. So, the present study was conducted to determine social health research priorities.   Methods: In the first step, important issues and research topics of social health were extracted from documents and studies conducted at the national level. In qualitative phase, reciprocating questionnaires were sent and interviews were conducted with experts and stakeholders, social health issues (as members of Delphi). In the next step, the research topics extracted were discussed in small groups (suggested by Council on Health Research for Development) to score the proposed priority topics by Delphi members. Finally, the list of priorities (titles that acquired more than 80% of the total score) was sent to Delphi members for final approval.   Results: During the study, 220 topics were obtained in four research domains: "description of the problem and its consequences", "cause finding", "intervention to eliminate or reduce problems", and "Management-Policymaking". Finally, 30 of these topics remained as priority topics. High priority research topics in social health were equity, happiness, economics, and ethics, respectively.   Conclusion: The findings provide a list of research priorities that help researchers carrying out studies that will have the greatest social health impact. Some targeting areas such as happiness and ethics were identified as less attended subjects that need more investment in research policies, management, and governance.